Metastasis of a basosquamous carcinoma arising in a nevus sebaceus - Ye, Qian; Shen, Xiao; Wang, Jie; Li, Feng‐Zeng; Fang, Sheng (Journal of cutaneous pathology, 2023)
Nevus sebaceus (NS) is a congenital hamartoma of skin structures including the epidermis, sweat sebaceous glands, and hair follicles. It is known that secondary tumors can occur in NS. However, secondary metastatic malignancies are rare. Basosquamous carcinoma (BSC) is an aggressive type of basal cell carcinoma (BCC) characterized by squamous differentiation. Herein, we report a case of metastatic BSC that developed in a 73‐year‐old male with NS. The clinical presentation of this patient was that of an ulcerative nodule developing in a longstanding plaque‐like lesion consistent with NS. Histopathological examination revealed characteristic features of BCC with some areas of squamous differentiation in addition to the structure of a typical NS. Immunohistochemical expression of Ber‐EP4, AE1/AE3, and epithelial membrane antigen helped to make the diagnosis of BSC.